Evaluating Department Chair and Student Leadership in Higher Education - Linda P. Thurston; B. Jan Middendorf (Educational Considerations, 2009)
In higher education, assessment of leadership capacities and performance of department chairs and students allows stakeholders to evaluate individuals and programs.
Keywords: funding; support; accountable; programs; assessment; evaluation; higher education